Proceedings of the 11th European Conference on Thermoelectrics ECT 2013 - Amaldi, Andrea; Tang, Francois; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
The Proceedings of the 11th European Conference on Thermoelectrics contains manuscripts from leading experts on topics spanning from material processing to applications in the field of thermoelectrics. The selected manuscripts also describe recent developments on measurement systems of thermoelectric properties, and the design and modelling of thermoelectric generators.
Effect of Structure and Microstructure on the Thermoelectric Properties of Yb0.19Co4Sb12 Alloy -- Thermoelectric Properties of Hot-Pressed K2Bi8-xSbxSe13 Materials -- Effect of Open Die Pressing on Chemical-Physical Properties of Zn4Sb3 Compound -- Phase Selection and Microstructure Refinement of Melt-Spun Zn4Sb3-Type Compound -- The Role Sodium Rich Pre-Treatments in the Enhanced Sintering of Sodium Cobalt Oxide Thermoelectric Ceramics -- Novel Process for Metal Silicide Nanostructures Regarding Cheap and Large Scale Material Synthesis -- A Flexible Measurement System for Characterization of Thermoelectric Materials -- A Comparison of Thermoelectric Devices Evaluation Results Obtained with a Harman Method Based and a Porcupine Method Based zT meters -- Sintered Nano-Ag as Joining Material for Thermoelectric Modules -- Anodized Aluminum as Effective and Cheap Alternative Substrate for Thermoelectric Generators -- Reliable Thermoelectric Generators for Space Missions -- Challenges in Dimensioning of an optimized thermoelectric Generator for Waste Heat Recovery in Cars -- Assessment of Thermoelectric Power Generation for Hybrid Electric Vehicles Based on Tracked Data -- Thermoelectric Generator for Low Temperature Applications -- Waste Heat Recovery in Steel Works Using Thermoelectric Generator -- Thermoelectric Generator Power Converter System Configurations: A Review -- Transient Thermal Response of Heat Sinks and Its Implication on Power Control Strategies -- Feasibility Study on Screen Printing as a Fabrication Technique for Low-Cost Thermoelectric Devices -- Improving Thermoelectric Cooling by Light Emission -- Simulation of Power Management Electronics and Energy Storage Unit for MEMS Thermoelectric Generator -- Experimental Validation of a Multiphysic Model for Optimization of Thermoelectric Generators -- Electrical and Configuration Characterization of Thermoelectric Generator Modules -- Modelica® Library for Dynamic Simulation of Thermoelectric Generators -- Modeling and Design Of Tubular Thermoelectric Generator used for Waste Heat Recovery.
Keywords: Materials science; Energy harvesting; Renewable energy resources; Nanotechnology; Characterization and Evaluation of Materials; Energy Harvesting; Renewable and Green Energy; Nanotechnology and Microengineering